Managing finance and resources in education - Coleman, Marianne; Anderson, Lesley (London : Paul Chapman, 2000)
This reference text for professionals concerned with the financial and resource management in all sectors of education is a set book for the MBA course at the Educational Management Development Unit at the University of Leicester.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Education -- Finance; Resource allocation; Education. -- Finance